POPULATION STUDY OF GANDARIA (Bouea macropylla Grifith) IN RUMAHTIGA VILLAGE, AMBON - Telussa, Ronald; Hiariej, Adriana; Lapu, Petrus (RUMPHIUS, 2020)
This research was conducted to determine the gandaria population and the factors that influence it. The method used was the 10 m X 10 m plot method, with a total of 240 plot plots at 7 different stations based on the presence of gandaria plants. There were 976 trees with a density value of 0.09 ind/m2 or ± 1 individual/11 m2, with a cluster distribution pattern. Factors that affect the gandaria population are the burning of the gandaria population area, land conversion by humans, changes in plant types and factors of increased population growth.